Critical Review On Waqf Experiences: Lessons From Muslim And Non-muslim Countries - Aimi Fadzirul Kamarubahrin; Abdullah Mohammed Ahmed Ayedh (Department of Islamic Economics, STAIN Kudus, 2024)
Non-Indexed Publication